Experimental Investigation of Mechanical Characterizations of a POM Fiber-Reinforced Mortar Material - Zhang, Jiuchang; Liu, Tianxi; Dong, Bo; Zhou, Suhua; Guo, Rongxin (Frontiers in Physics, 2022)
In this study, a new fiber: polyoxymethylene fiber (POMF), was added into cement mortar to make a POM fiber-reinforced mortar (POMF-RM) material. When designing the mix proportion of POMF-RM, two factors were considered: fiber length (4mm, 8mm and 12mm) and dosage of POMF (volume fraction 0.24%, 0.72% and 1.45%). When making the POMF-RM material, it was found that POMFs were easily dispersed into the mortar. Cubic and disc-shaped specimens of the POMF-RM material were made to conduct compression and Brazilian splitting experiments, respectively. It was found that, with increases in fiber length and volume content, the mechanical properties of the POMF-RM material were improved. Compared with the plain mortar, the elastic modulus, compressive and tensile strengths of the POMF-RM material significantly increased by 6.01%, 13.18% and 5.34% at least, respectively. Among these two factors, the length of POMF played a more positive role. It was observed that the POMFs could effectively prevent the expansion of tensile cracks and significantly inhibit the complete disintegration of mortar fragments. This study showed that POMF was an excellent reinforcement material worthy of further research and application in practical engineering.